Identification of Mutations in Members of the Connexin Gene Family as a Cause of Nonsyndromic Deafness in Taiwan - Yang, Jiann-Jou; Huang, Shih-Hsin; Chou, Kvei-Hsiu; Liao, Pei-Ju; Su, Ching-Chyuan; Li, Shuan-Yow (Audiology & neurotology, 2007)
Connexins (Cx), a large family of membrane proteins, are key components of gap junction channels. These channels are critical intercellular pathways through which ions or small molecules are passed, regulating a variety ofphysiological and developmental processes. One of these processes is hearing. In the current study, a genetic survey was made on 380 Taiwanese individuals, 260 with nonsyndromic deafness and 120 with normal hearing. All the 380 Taiwanese were screened for the presence of mutations in 8 genes of the Cx gene family. These genes included Cx26 (GJB2), Cx29 (GJE1), Cx30 (GJB6), Cx30.3 (GJB4), Cx31 (GJB3), Cx32 (GJB1), Cx43 (GJA1) and pseudogene [ρ] of Cx43 (ρ GJA1). Mutations were identified in 7 out of the 8 screened genes of the Cx family from 62 of the 260 deaf subjects (23.85%). Of the 17 mutations observed in the Cx gene family, 11 were novel mutations. Fourteen polymorphisms that were not associated with hearing loss were identified in the Cx gene family. The first 2 most frequently occurring mutations were found in the Cx26 (28/62; 45.16%) and the ρ Cx43 (17/62; 27.42%), respectively. Nine cases of mutations were found in the Cx30.3 (9/62; 14.52%). In the Cx30, 1 novel mutation was identified in 1 case (1/62; 1.61%). Two patients with mutations of each of Cx29 and Cx43 were found (2/62; 3.23%). One novel mutation of Cx31 was identified in 3 patients with nonsyndromic deafness (3/62; 4.84%). The Cx32 was the only gene without detecting any mutation or polymorphism.Our study provides information for understanding the importance of genetic factors in nonsyndromic deafness of the Taiwanese and may be of use in the improvement of genetic diagnosis of hearing loss in Taiwan.